2017
DOI: 10.1242/bio.024562
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-osteoarthritis effects of tectorigenin

Abstract: Osteoarthritis (OA) is a common and dynamic disease of the joints, including the articular cartilage, underlying bones and synovium. In particular, OA is considered as the degeneration of the cartilage. Tectorigenin (Tec) is known to affect many biological processes; however, its effects on articular chondrocytes remain unclear. This study aimed to assess the effects of Tec on articular cartilage. In vitro, Tec inhibited the expression levels of type X collagen, cyclooxigenase-2, matrix metalloproteinase (MMP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Tectorigenin (Tec; Figure a), a component of Belamcanda Adans, has antiproliferation, anti‐inflammatory, and antioxidant activities (Wang et al, ). Presently, the main studies on Tec have focused on its antitumor effects via the NF‐κB and MAPK pathways (Yang et al, ; Zeng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tectorigenin (Tec; Figure a), a component of Belamcanda Adans, has antiproliferation, anti‐inflammatory, and antioxidant activities (Wang et al, ). Presently, the main studies on Tec have focused on its antitumor effects via the NF‐κB and MAPK pathways (Yang et al, ; Zeng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…22,25 It has been reported in other studies that tectorigenin inhibit activation of NF-κB on other cells. 15,26,27 In this study, we evaluated the activation of NF-κB signalling in the tectorigenin treatment on BMM cells. Our data demonstrated that tectorigenin could inhibit degradation of IκBα and phosphorylation of NF-κB p65…”
Section: Discussionmentioning
confidence: 99%
“…Its potential usage in anti-inflammatory and antioxidant activity was reported before, 13,14 and more specifically, its anti-inflammatory effect in osteoarthritis and NF-κB signalling blockage. 15 In this study, the effect of tectorigenin on RANKL-induced NF-κB activation and osteoclastogenesis was investigated in vitro, plus its anti-osteoporosis action in an ovariectomized (OVX) mice model. β-actin (SC-47778) antibodies was purchased from Santa Cruz Biotechnology.…”
mentioning
confidence: 99%
“…In OA chondrocytes, resveratrol may reverse the decrease in the levels of type II collagen, aggrecan, and glycosaminoglycan by regulating silent information regulator 2 type 1, hypoxia-inducible factor-2α, and MMPs expression [24,62,63,77]. Curcumin [28], naringin [42], icariin [16,78,79], berberine [68,69], sinomenine [72], tetramethylpyrazine [13,70,80], astragaloside IV [81], halofuginone [82], puerarin [83], quercetin [84], celastrol [54,85], harpagoside [32], ferulic acid [55], shikonin, acetylshikonin [86], ginsenoside Rb1 [76,87], cinnamophilin [30], honokiol [50], 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-d-glucoside [60], geniposide [31], ginsenoside Rg5 [74], cryptotanshinone [29], isofraxidin [33], paeonol [56], crocin [43], coptisine [44], piperine [45], butein [46], licochalcone A [36], tectorigenin [48], theaflavin-3,3′-digallate [59], anemonin [49], gastrodin [51], compound K…”
Section: The Effects Of Bioactive Components On Cartilage In Oamentioning
confidence: 99%
“…Emodin ameliorates OA cartilage inflammation by inhibiting NF-κB and Wnt/β-catenin signaling [ 38 , 39 ]. NF-κB signaling pathway is also involved in the treatment of cartilage inflammation by icariin [ 40 , 41 ], arasaponin R1 [ 41 ], berberine [ 17 ], tetramethylpyrazine [ 13 ], naringin [ 42 ], crocin [ 43 ], coptisine [ 44 ]; piperine [ 45 ], butein [ 46 ]; kaempferol [ 47 ], tectorigenin [ 48 ], anemonin [ 49 ], honokiol [ 50 ], and gastrodin [ 51 ]. In addition, some molecules have been reported to reduce the expression of inflammatory factors in OA cartilage, but the related pathways still need to be further explored, such as astragaloside IV [ 52 ], puerarin [ 53 ], celastrol [ 54 ], ferulic acid [ 55 ], paeonol [ 56 ], artesunate [ 57 ], genistein [ 58 ], theaflavin-3,3′-digallate [ 59 ], and 2, 3, 5,4′-tetrahydroxystilbene-2-O-β- d -glucoside [ 60 ].…”
Section: The Anti-oa Activities Of Bioactive Components From Herbal Mmentioning
confidence: 99%